Strontium isotope evidence for prehistoric migration at Chokepukio, Valley of Cuzco, Peru - Andrushko, V.A.; Buzon, M.R.; Simonetti, A.; Creaser, R.A. (Latin American Antiquity, 2009)
Although Spanish chroniclers referred frequently to coerced migration in the Inca Empire, these migrations have been difficult to document archaeologically. One approach to migration studies, strontium isotope (87Sr/86Sr) analysis, has emerged as an effective technique. Until now, however, this method has not been applied to the Inca heartland region of Cuzco, Peru. In this study, we use strontium isotope analysis to examine patterns of prehistoric migration in the Cuzco Valley. Human dental enamel samples from the Cuzco Valley site of Chokepukio are analyzed and compared to the local 87Sr/86Sr signature established through faunal specimens. Though tentative due to a small sample size, the isotope results do not provide evidence for migration at this site from the time periods preceding the rise of the Inca Empire (200 B.C. to A.D. 1400). In contrast, there is substantial evidence for migration during the time of Inca imperialism (A.D. 1400-1532). Among these migrants, variation in 87Sr/86Sr values suggests that individuals emigrated from geologically diverse locations, while sex differences in the migrant group include a higher percentage of females and a greater diversity in female 87Sr/86Sr values. These data, along with ethnohistoric evidence, reveal how Inca labor policies reconfigured the composition of populations in the imperial heartland. Copyright ©2009 by the Society for American Archaeology.
45 citations (Crossref) [2023-10-31]
Keywords: dept.ant

The discursive construction of the german welfare state: interests and institutionality - McGill, Kenneth (Journal of Linguistic Anthropology, 2009)
This article consists of an initial theoretical attempt to describe “interests” as widespread social phenomena which emerge specifically from discursive interaction. I focus on the way in which the indexical signaling of discourse participation roles and public/private standings provide key conditions of possibility for the emergence of interests in interactional real time. The case at hand involves the German welfare state, a social institution which is constituted both on the local level of my fieldsite (a working-class suburb of the former East Berlin) and on the national level (through the popular media and through the circulation of laws, policy documents and the like). [Germany, welfare state, interests, indexical orders, institutionality].
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/101-266-632-180-303 tex.unique-id: [object Object]
Keywords: Germany; Indexical orders; Institutionality; Interests; Welfare state; dept.ant

The causes of porotic hyperostosis and cribra orbitalia: A reappraisal of the iron-deficiency-anemia hypothesis - Walker, Phillip L.; Bathurst, Rhonda R.; Richman, Rebecca; Gjerdrum, Thor; Andrushko, Valerie A. (American Journal of Physical Anthropology, 2009)
Porosities in the outer table of the cranial vault (porotic hyperostosis) and orbital roof (cribra orbitalia) are among the most frequent pathological lesions seen in ancient human skeletal collections. Since the 1950s, chronic iron-deficiency anemia has been widely accepted as the probable cause of both conditions. Based on this proposed etiology, bioarchaeologists use the prevalence of these conditions to infer living conditions conducive to dietary iron deficiency, iron malabsorption, and iron loss from both diarrheal disease and intestinal parasites in earlier human populations. This iron-deficiency-anemia hypothesis is inconsistent with recent hematological research that shows iron deficiency per se cannot sustain the massive red blood cell production that causes the marrow expansion responsible for these lesions. Several lines of evidence suggest that the accelerated loss and compensatory overproduction of red blood cells seen in hemolytic and megaloblastic anemias is the most likely proximate cause of porotic hyperostosis. Although cranial vault and orbital roof porosities are sometimes conflated under the term porotic hyperostosis, paleopathological and clinical evidence suggests they often have different etiologies. Reconsidering the etiology of these skeletal conditions has important implications for current interpretations of malnutrition and infectious disease in earlier human populations. Am J Phys Anthropol 139:109-125, 2009. (C) 2009 Wiley-Liss, Inc.
448 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/098-991-013-073-31X tex.eissn: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Age Factors; Anemia; Archaeology; Cribra orbitalia; Fossils; History; Medieval; Humans; Hyperostosis; Nutritional Physiological Phenomena; Orbit; Paleopathology; Porosity; Porotic hyperostosis; Skull; age distribution; cribra orbitalia; dept.ant; diarrhea; erythropoiesis; fossil human; gastrointestinal infection; hemolytic anemia; human; hyperostosis; intestine parasite; iron deficiency anemia; iron intake; malnutrition; megaloblastic anemia; paleopathology; peer-reviewed; porotic hyperostosis; review

From nothing to something: the appearance and context of the earliest archaeological record - Rogers, Michael J.; Semaw, Sileshi (Sourcebook of Paleolithic Transitions: Methods, Theories, and Interpretations, 2009)
Before 2.6 million years ago (Ma), no archaeological record has been securely documented, and therefore there is no evidence of hominin tool use. Then, at 2.6–2.58 Ma, there is widespread evidence for tool manufacture and use at several archaeological sites, with undisputed stone tools and fossil fauna at Gona, Ethiopia. Additionally, the evidence from the earliest archaeological sites at Gona shows that the earliest stone tool makers were skilled flintknappers and were able to select high quality stone raw materials. The possible reasons behind this seeming abrupt transition from the absence of stone tools to the presence thereof include sampling biases, paleogeographic influences, gaps in the geological record, paleoenvironmental change, and changes in the record of hominin evolution.Based on our observations at Gona, the earliest use of flaked stone tools is likely to be slightly older than 2.6 Ma. These stone tools represent a significant change in behavior that set the stage for subsequent hominin evolution. The paleogeographic and paleoenvironmental evidence points to the earliest use of stone tools in certain settings: usually (but not always) close to raw material sources, and ecotones between riparian woodlands and open grasslands. The earliest stone tool makers were proficient, selective, and flexible in their reduction strategies. The variability we see in Pliocene artifact assemblages has much to do with different raw material sources.
Citation Key Alias: lens.org/168-317-279-402-478
Keywords: Early Stone Age; Gona; Oldowan; Paleoenvironments; Pliocene; Stone tools; dept.ant

The Oldowan-Acheulian Transition: Is there a “Developed Oldowan” Artifact Tradition? - Semaw, Sileshi; Rogers, Michael; Stout, Dietrich (Sourcebook of Paleolithic Transitions: Methods, Theories, and Interpretations, 2009)
The phrase “Developed Oldowan” (DO) was originally coined by M. Leakey to describe a technologically “advanced Oldowan” artifact tradition, that preceded the Acheulian Industry. M. Leakey further identified three stages of the DO which she labeled as the DOA, DOB and DOC. The DO (sensu lato) has been generally recognized as transitional to the Acheulian, but the status of the DOB and the DOC remains unclear. In addition to a lack of clarity in terms of classification, the DO also suffers from a lack of secure radiometric dates, even at Olduvai where it was first identified. Despite such shortcomings, archaeologists still assign assemblages into the DO, as supposedly “intermediate” or transitional between the Oldowan and the Acheulian. However, a closer look at the DO assemblages from Olduvai Gorge and other sites in Africa and the Middle East shows that the artifacts assigned into this tradition are not technologically drastically different from the preceding Oldowan. Probably the flaking characteristics of the raw material types (e.g., quartzite and limestone, and to a lesser extent basalt) and the original shape of the cobbles used by hominins may have played a major role in the final shape of the “distinctive” artifact types (such as spheroids/subspheroids) used for assigning assemblages into the DO. Further, both the DOB and the Acheulian appeared ˜1.7 million years ago (Ma) in the archaeological record, making it unlikely that the DO is a transitional artifact tradition that preceded the Acheulian. Our preliminary evaluation of the archaeological record at Gona, Ethiopia and elsewhere suggests a fairly abrupt appearance of the Acheulian after a temporally rapid transition from the Oldowan.
Citation Key Alias: lens.org/001-307-927-954-428
Keywords: Developed Oldowan; Early Acheulian; Oldowan; Oldowan-Acheulian transition; dept.ant